REVITALIZING THERAPEUTICS: DRUG REPURPOSING AS A COST-EFFECTIVE STRATEGY FOR DRUG DEVELOPMENT - MAKHIJANI, SHIVANI (International Journal of Applied Pharmaceutics, 2024)
The process of developing new drugs is known for being drawn-out, expensive, risky, and having a high attrition rate. Drug repurposing has grown in favor recently as a practical way to speed up the development of new medicines while reducing the costs and time constraints associated with traditional drug research. The description of this study's pharmacological repurposing highlights its promise as a practical method to fill gaps in the market and revitalize treatment options. This review provides a full analysis of the ground-breaking tactic of repurposing medications, supported by numerous cases that demonstrate its revolutionary potential. We examine instances of repurposed drugs, such as thalidomide, sildenafil, and metformin, that have performed astoundingly well in a range of therapeutic settings despite being used outside of their original scope. Overall, the paper's main goal-to study pharmacological repurposing as a potentially successful strategy for revitalizing treatments-is, succinctly summarized in this abstract. It highlights the potential benefits of this approach and how it might be used in the pharmaceutical industry's ongoing quest for more inexpensive and effective medicine development.